Unexplained isolated acute severe thrombocytopenia after surgery for a recurrent malignant retroperitoneal tumor presenting with colon perforation: A case study of a disastrous complication. (2020) - Boulas, K.A.; Paraskeva, A.; Triantafyllidis, A.; Hatzigeorgiadis, A.
Highlights: Thrombocytopenia in cancer patients is correlated with poor prognosis. Drugs, sepsis, HIT, DIC, ITP are the most common causes of postoperative thrombocytopenia. Prompt diagnosis is essential as management varies considerably depending on etiology. Secondary ITP has not previously been associated with a retroperitoneal tumor. Kasabach-Merritt syndrome has not previously been associated with a retroperitoneal tumor. Abstract: Introduction: Tumor- or treatment- induced thrombocytopenia in solid cancer patients is common. In the postoperative setting, diagnosis of thrombocytopenia become more complex as infection, sepsis, drugs and transfusion come also into the equation. Presentation of case: Herein, the case an otherwise-healthy 71-year-old male patient with a sizable recurrent malignant retroperitoneal tumor under pazopanib admitted with colon perforation and submitted to emergency left colectomy with end transverse colostomy is presented. Immediate postoperative period characterized by massive primary tumor growth and isolated acute severe thrombocytopenia. The patient treated with combined prednisone, IVIg and platelets transfusion along with medication discontinuation with no response. Discussion: Sepsis-, drug- and heparin-induced thrombocytopenia, disseminated intravascular coagulopathy and secondary (sepsis-, drug-, transfusion- or tumor-induced) immune thrombocytopenia (ITP) were included in the differential diagnosis. Based on exclusion, secondary drug- or tumor-induced ITP was the most prominent diagnosis. Concomitant presentation of thrombocytopenia along with massive primary tumor growth made Kasabach-Merritt syndrome also a probable diagnosis. However, neither secondary ITP nor Kasabach-Merritt syndrome has previously been associated with a retroperitoneal tumor in the literature. Conclusion: Although management of thrombocytopenia depends on etiology, in our patient's case the diagnosis of secondary ITP and directed management did not result in a successful outcome.